Simultaneous determination of chlorpheniramine maleate, phenylephrine hydrochloride, paracetamol and caffeine in pharmaceutical preparation by RP-HPLC - Redasani V.K.; Gorle A.P.; Badhan R.A.; Jain P.S.; Surana S.J. (Chemical Industry and Chemical Engineering Quarterly, 2013)
Reversed-phase High-Performance Liquid-Chromatography (RP-HPLC) method was successfully developed for the simultaneous determination of quaternary mixture consisting of chlorpheniramine maleate (CPM), phenylephrine hydrochloride (PE), paracetamol (PCM) and caffeine in pharmaceutical preparation. The method was found to be simple, sensitive and rapid. The separation of the drugs was carried out using Inertsil ODS C18 column using 0.05M dibasic phosphate buffer: acetonitrile (93: 07; v/v) as mobile phase. The flow rate of mobile phase was adjusted to 1.5 ml/min and column oven temperature was kept at 30ᴼC. All these drugs were resolved successfully with retention times 2.74 (CPM), 3.48(PE), 9.5(PCM) and 26.32(Caffeine) minutes when detection was carried out at 215 nm. Correlation coefficient was found 0.999, 0.998, 0.999 and 0.999 respectively for CPM, PE, PCM and Caffeine. The relative standard deviation in the tablets was found less than 2% for six replicates. The method was validated for precision and accuracy. Thus, proposed method can be successfully applicable to the pharmaceutical preparation containing the above mentioned drugs without any interference of excipients.